2018
DOI: 10.2217/fvl-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Post-Translational Modifications of Coronavirus Proteins: Roles and Function

Abstract: Post-translational modifications (PTMs) refer to the covalent modifications of polypeptides after they are synthesized, adding temporal and spatial regulation to modulate protein functions. Being obligate intracellular parasites, viruses rely on the protein synthesis machinery of host cells to support replication, and not surprisingly, many viral proteins are subjected to PTMs. Coronavirus (CoV) is a group of enveloped RNA viruses causing diseases in both human and animals. Many CoV proteins are modified by PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
217
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(232 citation statements)
references
References 205 publications
1
217
0
1
Order By: Relevance
“…Very little information is available on the glycosylation of CoV E and its role. The IBV E protein has been suggested to contain a single glycosylation site in its luminal N-terminus, while SARS-CoV E has been predicted to contain two potential glycosylation sites [132]. Based on the topology of IBV E, Corse and Machamer [60] proposed that it could be glycosylated on asparagine residue five (N5) of the Nterminus.…”
Section: Glycosylationmentioning
confidence: 99%
“…Very little information is available on the glycosylation of CoV E and its role. The IBV E protein has been suggested to contain a single glycosylation site in its luminal N-terminus, while SARS-CoV E has been predicted to contain two potential glycosylation sites [132]. Based on the topology of IBV E, Corse and Machamer [60] proposed that it could be glycosylated on asparagine residue five (N5) of the Nterminus.…”
Section: Glycosylationmentioning
confidence: 99%
“…Coronavirus M proteins are invariably glycosylated in the luminal ectodomain. While the M protein of some lineage A Betacoronaviruses is O-linked glycosylated, those of other coronaviruses are exclusively Nlinked (Fung and Liu, 2018). Only a single N-glycosylation site has been identified in the SARS-CoV M protein at N4 (Hu et al, 2003;Voss et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although IBV M protein is presumably post-translationally inserted into the ER membrane, N-linked glycosylation of its ectodomain is nonetheless dependent on modification enzymes inside the ER lumen (Fung and Liu, 2018). We have previously shown that IBV infection activates the PERK-eIF2α and IRE1-XBP1 branches of the UPR signaling pathway.…”
Section: Effect Of N3d/n6d Mutations On Ibv-induced Er Stress Responsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 There are significant post-translational modifications in the S protein. The spike protein ectodomain is heavily glycosylated with heterogeneous N-linked glycans 19 and exists in a prefusion and a postfusion conformation. The oligosaccharides could influence priming by host proteases and determine antibody recognition.…”
Section: (A Class I Viral Fusion Protein Is a Viral Protein Primed Bymentioning
confidence: 99%